Encapsulation of Red Chili Powder Using Arabic Gum as a Coating Agent - Dharia Renate; Windika Pebryanti; Edhita Renesteen (agriTECH, 2026)
Red chili (Capsicum annuum L.) powder is highly susceptible to degradation due to the instability of capsaicin, its primary bioactive compound. Therefore, this study aims to evaluate the effect of Arabic gum concentrations as a coating agent on the physicochemical characteristics of encapsulated red chili powder. The study procedures were carried out using a Completely Randomized Design (CRD) with 6 levels of Arabic gum concentration, such as 0% as a control, 0.3%, 0.6%, 0.9%, 1.2% and 1.5%. Data were then analyzed using Analysis of Variance (ANOVA) at the 1% and 5% levels to determine the effect among treatments. Subsequently, the analysis was followed by Duncan’s New Multiple Range Test (DNMRT) at the 5% significant level. The results showed that Arabic gum significantly affected encapsulation performance. The optimal treatment was obtained at 0.9% Arabic gum, with a yield of 74.01% and color parameters of L 33.07, a* 19.33, and b* 14.33. Moisture content, solubility, encapsulated capsaicin (CE), total capsaicin (CT), and encapsulation efficiency were 12.83%, 83.61%, 0.73 mg/g, 7.85 mg/g, and 9.26%, respectively. In conclusion, the use of Arabic gum at a concentration of 0.9% effectively enhanced physical and chemical stability of red chili powder through improved encapsulation characteristics. These results confirm its potential as a functional encapsulating agent in spice powder formulation, particularly for applications in food and nutraceutical industries.